BERKARYA MUSIK: ANTARA HARAPAN DAN TANTANGAN - Mr. Warsana (Institut Seni Indonesia Yogyakarta, 2012)
It is not easy to create musical works. It requires perseverance, toughness, broad knowledge and experience in addition to long creative process for musicians to pour their ideas into musical works that are intelligible and enjoyable. Different artists have different understanding of artistic works with certain theme and they have their own way to interpret the artistic works. There are various challenges they artists must face in creating good artistic works that are enjoyable by their audience or music lovers. The creative process is carried out by exploring, observing, improvising and arranging the results of the exploration, the observation and the improvisation in a good composition. It is the key for the artists to the success in their artistic creation. Keywords: Music, Creativity, Performance